2003
DOI: 10.1038/sj.bjc.6601264
|View full text |Cite
|
Sign up to set email alerts
|

Soluble form of carbonic anhydrase IX (CA IX) in the serum and urine of renal carcinoma patients

Abstract: Tumour-associated protein carbonic anhydrase IX (CA IX) has two major forms. One is a cell-associated, transmembrane protein seen on Western blots as a twin band of 54/58 kDa, expressed in gastric mucosa and in several types of cancer. The other is a soluble protein s-CA IX of 50/54 kDa, which is released into the culture medium or into the body fluids, most likely by proteolytic cleavage of the extracellular part from transmembrane and intracellular sequences. While TC media of CA IX-positive tumour cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
91
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(100 citation statements)
references
References 12 publications
7
91
1
1
Order By: Relevance
“…Nevertheless, we showed that the plasma CAIX detected in patients with NSCLC is much lower than CAIX concentrations described in renal cell carcinoma, because the very high constitutive HIF-1a levels in these latter tumours and also differences in CAIX expression depending on the cell type (Li et al, 2008). Increased levels of plasma CAIX have been reported only in urological cancers (Zavada et al, 2003;Li et al, 2008;Hyrsl et al, 2009). Thus, our report is the first study to show evidence of high CAIX levels in the plasma of NSCLC patients.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Nevertheless, we showed that the plasma CAIX detected in patients with NSCLC is much lower than CAIX concentrations described in renal cell carcinoma, because the very high constitutive HIF-1a levels in these latter tumours and also differences in CAIX expression depending on the cell type (Li et al, 2008). Increased levels of plasma CAIX have been reported only in urological cancers (Zavada et al, 2003;Li et al, 2008;Hyrsl et al, 2009). Thus, our report is the first study to show evidence of high CAIX levels in the plasma of NSCLC patients.…”
Section: Discussionmentioning
confidence: 52%
“…This corresponds to the extracellular part of the CAIX molecule, which is composed of the proteoglycan (PG)-like and CA domains that are cleaved off the plasma membrane (Zavada et al, 2003). Our study reports that the plasma CAIX level in NSCLC patients is significantly higher than in healthy individuals (Po0.001).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Its extracellular portion contains a large CA domain, which is N-terminally extended with a proteoglycan (PG)-like region, and via a single-pass transmembrane (TM) region is linked to a short C-terminal intracytoplasmic (IC) tail (Pastorek et al, 1994;Opavsky et al, 1996). The extracellular domain (ECD) of CA IX can be released into the cell culture medium or into the body fluids of tumour patients (Zavada et al, 2003). Concentration of CA IX ECD in the blood and urine varies in a wide range and shows no obvious correlation with the tumour size, at least in patients with renal cell carcinomas.…”
mentioning
confidence: 99%
“…Túto rozpustnú extracelulárnu doménu CA IX je možné ľahko detekovať v telesných tekutinách pacienta, pomocou metódy ELISA alebo metódou Western blot. Rozpustná forma CA IX sa rýchlo odstraňuje z krvi vylučovaním nezmeneného proteínu do moču a jeho proteolytickou degradáciou [24]. Dôležitým poznatkom je, že v podmienkach hypoxie zostáva rýchlosť bazálneho uvoľňo-vania extracelulárnej domény CA IX nezmenené, a preto zvýšené množstvo CA IX zaznamenané v extracelulárnom priestore a v telesných tekutinách odráža jeho zvýšenú tvorbu v hypoxických bunkách [25].…”
Section: Odber a Vyšetrovanie Bio Logického Materiáluunclassified